An Overview of Research on Hagiographies in Slovenian Literary Studies - Požin, Karin (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The article provides an overview of the research of hagiographies within Slovenian literary studies to date, and outlines current research perspectives. The main prem-ise stems from the observation that, despite the presence of saints’ biographies in the field of Slovenian literary sciences, these texts have, from the early nineteenth century to the present, often been overlooked among literary scholars, and regarded as insufficiently “literary” to be acknowledged as a legitimate subsystem within the broader system of Slovenian literature. Only in recent years have hagiogra-phies and various manifestations of hagiographic discourse begun to emerge in Slovenia as independent and systematically examined objects of scholarly inquiry.